Phenotypic characterization of exotic tomato germplasm: An excellent breeding resource. - Zeshan Hassan (Public Library of Science (PLoS), 2021)
Tomato production in Pakistan faces significant problems of low yields due to various biotic and abiotic stresses primarily because of a narrow genetic base of the cultivars being used. Therefore, Introduction and evaluation of the exotic tomato germplasm has become necessary to acquire elite material to develop future breeding programs. To this end, the present study was conducted for the phenotypic characterization of twenty exotic tomato genotypes along with two locally grown cultivars in semi-arid subtropical climate. Data were collected for morphological, fruit quality and fruit yield traits. A significant (p<0.05) phenotypic variation was observed for all the studied traits. Maximum yield was obtained from "Rober" i.e., 1508.31 g per plant. The maximum shelf life was observed in the Cromco, with the least weight loss (2.45%) and loss in the firmness of fruit (22.61%) in 4 days. Correlation analyses revealed a strong genetic association among morphological and yield related traits. High estimates of the heritability (ranged from 79.77% to 95.01% for different traits), along with a high genetic advance (up to 34%) showed the potential usefulness of these traits and genotypes to develop breeding programs to improve the tomato yield and fruit quality.